A study on factors of organizational culture that affect total quality management in Steelcase Manufacturing (Malaysia) / Nurul Syakinah Azizan - Azizan, Nurul Syakinah (2015)
This research is designed to study on factors a study on factors of organizational culture that affect total quality management in Steelcase Manufacturing (Malaysia). The research consists of three factors which are connection with management, motivation from management and task control. The objective of this study is to to determine the relationship between connection with management, motivation from management, task control and the effectiveness of TQM and also to identify the most significant factor affecting TQM. Questionnaire was distributed among 51 respondents from the chosen population. The findings of the study show that all independent variables have a significant relationship with the dependent variable. Other than that, task control was proven to be most significant out of the three variables. The researcher managed to achieve all the objectives of the study.